THE CONCEPT OF THE SUBJECT OF CRIME IN MODERN CRIMINAL LAW: PROBLEMS IN THE CONTEXT OF DIGITAL TRANSFORMATION AND NEW SOCIAL RELATIONS - Noraliyev Turgun (International Journal of Business, Law and Political Science, 2026)
Objective: This article provides a systematic analysis of the concept of the subject of crime in modern criminal law, its place, and its role in the structure of social relations. In the context of the fourth industrial revolution, digitalization, and the dynamic development of artificial intelligence, it is scientifically substantiated that the subject of crime should not be limited only to traditional material goods but should fully encompass intangible goods, including information, digital assets, energy resources, as well as human organs. Method: The article also provides a comparative analysis of the opinions of domestic and foreign scholars, expressing the author’s personal attitude and critical view on existing scientific discussions. Results: The author criticizes the outdated views that the subject of crime is merely a component of the object of crime or a sign of the objective side, and puts forward his conceptual approach to recognizing it as an independent and equal element of the corpus delicti. As a result of the research, specific, comprehensive, and scientifically grounded proposals and recommendations consisting of six points have been developed to improve criminal legislation and eliminate confusion arising in law enforcement practice. Novelty: These recommendations will serve the correct qualification of cybercrimes and offenses involving high technologies in the future.